The Long-Term Impacts of International Migration: Evidence from a Lottery - John Gibson; David McKenzie; Halahingano Rohorua; Steven Stillman (Institute for the Study of Labor (IZA), 2015)
We examine the long-term impacts of international migration by comparing immigrants who had successful ballot entries in a migration lottery program, and first moved almost a decade ago, with people who had unsuccessful entries into those same ballots. The long-term gain in income is found to be similar in magnitude to the gain in the first year, despite migrants upgrading their education and changing their locations and occupations. This results in large sustained benefits to their immediate family, who have substantially higher consumption, durable asset ownership, savings, and dietary diversity. In contrast we find no measureable impact on extended family.
Keywords: F22; O15; 330; international migration; natural experiment; assimilation; household well-being